2002
DOI: 10.2131/jts.27.423
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Kojic Acid on Thyroidal Functions in Rats by Single-Dose Administration and in Cultured Rat Thyroid Cells (Frtl-5 Cells)

Abstract: -The effects of kojic acid (KA) on thyroidal function were studied by single-dose administration in rats and in cultured rat thyroid cells . In rats receiving a single dose of 1,000 mg/kg KA orally, the 125 I uptake from blood into the thyroid gland was significantly lower than that of the control group from 30 min to 24 hr after administration. The 125 I organification activity of the KA groups was significantly lower than control from 30 min to 6 hr after administration. However, the 125 I organification act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 12 publications
1
9
0
Order By: Relevance
“…Evidence indicating formation of DNA adducts in the thyroids of rats given diet containing 2% KA for 2 weeks was lacking (Tamura et al -ing to DNA damage was not induced. As for modifying effects of KA on thyroidal function, inhibition of iodine KA at a massive dose or for a long administration period (Tamura et al, 1999b;Higa et al, 2002). The present and previously reported results thus indicate that carcinogenic effects of KA in the rat thyroid are associated with inhibi--roid, and it can be concluded that thyroid tumors were induced via promoting effects.…”
Section: Discussionsupporting
confidence: 60%
“…Evidence indicating formation of DNA adducts in the thyroids of rats given diet containing 2% KA for 2 weeks was lacking (Tamura et al -ing to DNA damage was not induced. As for modifying effects of KA on thyroidal function, inhibition of iodine KA at a massive dose or for a long administration period (Tamura et al, 1999b;Higa et al, 2002). The present and previously reported results thus indicate that carcinogenic effects of KA in the rat thyroid are associated with inhibi--roid, and it can be concluded that thyroid tumors were induced via promoting effects.…”
Section: Discussionsupporting
confidence: 60%
“…[4][5][6][7] Used as an important material in antibiotic and pesticide productions, 3,8,9) kojic acid has been shown to act as a competitive and reversible inhibitor of animal and plant polyphenol oxidases, xanthine oxidase, and D-and some L-amino acid oxidases. [10][11][12][13][14][15][16] About the toxicological aspect, the acute or subchronic toxicity resulting from an oral dose of kojic acid has never been reported, but convulsions may occur if kojic acid is injected. Continuous administration of high doses of kojic acid in mice resulted in induction of thyroid adenomas in both sexes.…”
mentioning
confidence: 99%
“…There are some well-known melanin synthesis inhibitors, including kojic acid, arbutin, PTU or hydroquinone, which are being utilized globally as cosmetics ingredients at present. However, these melanogenic inhibitors may induce human skin tumorigenicity at high concentration doses or frequent use (26)(27)(28). There are concentration standards for every country to use kojic acid, arbutin or other chemical ingredients as a composition in cosmetic additives.…”
Section: Discussionmentioning
confidence: 99%